TAKALINTAR MEDIA AND CONCRETE LEARNING EXPERIENCES IN MULTIPLICATION LEARNING: A PHILOSOPHICAL ANALYSIS BASED ON DALE’S CONE OF EXPERIENCE FOR GRADE III STUDENTS OF SDN BANDUNG 2 JOMBANG - Ichdah Maslichah, Nora; Zahrani Susilo, Claudya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Takalintar media as a learning tool in improving students’ understanding of multiplication concepts in elementary school mathematics learning. The study focuses on examining students’ learning experiences through the perspective of Edgar Dale’s Cone of Experience, which emphasizes the importance of concrete learning experiences in the learning process. This research used a qualitative approach with a philosophical analysis method. The research was conducted in Grade III at SDN Bandung 2 Jombang. Data were collected through observation of learning activities, documentation of the teaching and learning process, and literature review related to learning media, experiential learning, and mathematics education. The data were analyzed using qualitative descriptive analysis through the stages of data reduction, data organization, interpretation, and conceptual synthesis. The findings indicate that the use of Takalintar media provides concrete, visual, and interactive learning experiences that help students understand multiplication concepts more effectively. Based on Dale’s Cone of Experience, Takalintar media facilitates learning experiences that move from abstract verbal explanations toward more demonstrative and visual learning activities. These learning experiences encourage students to actively explore multiplication patterns, participate in discussions, and develop conceptual understanding of mathematical relationships. Therefore, the use of Takalintar media can contribute to the development of meaningful mathematics learning by supporting experiential learning and enhancing students’ conceptual understanding of multiplication in elementary school.